Clinical Characteristics of Spinal Levobupivacaine: Hyperbaric Compared with Isobaric Solution - Vimolluck Sanansilp; Travuth Trivate; Phakaporn Chompubai; Shusee Visalyaputra; Pattipa Suksopee; Ladda Permpolprasert; Benno von Bormann (The Scientific World Journal)
We performed a prospective, double-blinded study in 20 patients undergoing gynecologic surgery with lower abdominal incision, to investigate characteristics of intrathecal hyperbaric levobupivacaine compared with isobaric levobupivacaine. We randomly assigned them to receive 3 mL of either isobaric or hyperbaric 0.42% levobupivacaine intrathecally. We found that hyperbaric levobupivacaine, compared with isobaric levobupivacaine, spread faster to T10 level (2.8 ± 1.1 versus 6.6 ± 4.7 minutes, 𝑃=0.039), reached higher sensory block levels at 5 and 15 minutes after injection (T8 versus L1, 𝑃=0.011, and T4 versus T7, 𝑃=0.027, resp.), and had a higher peak level (T4 versus T8, 𝑃=0.040). Isobaric levobupivacaine caused a wider range of peak levels (L1 to C8) compared with hyperbaric form (T7 to T2). The level of T4 or higher reached 90% in the hyperbaric group compared with 20% in the isobaric group (𝑃=0.005). Our results suggest that hyperbaric levobupivacaine was more predictable for sensory block level and more effective for surgical procedures with lower abdominal approach. Hyperbaric levobupivacaine seems to be suitable, but the optimal dosage needs further investigation.